2012
DOI: 10.1002/btpr.1534
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dynamic changes in the proteome of a Bcl‐XL overexpressing Chinese hamster ovary cell culture during exponential and stationary phases

Abstract: Mammalian cell cultures used for biopharmaceutical production undergo various dynamic biological changes over time, including the transition of cells from an exponential growth phase to a stationary phase during cell culture. To better understand the dynamic aspects of cell culture, a quantitative proteomics approach was used to identify dynamic trends in protein expression over the course of a Chinese hamster ovary (CHO) cell culture for the production of a recombinant monoclonal antibody and overexpressing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…Although the optimal organic solvent concentration is less than typically used for CHO lysate precipitation [25, 26], this finding agrees with previous reports that 50% acetone is sufficient to precipitate most proteins greater than 20 kDa [21]. Conversely, Thongboonkerd et al have shown that a final organic solvent concentration of 90% was required to optimally precipitate urinary proteins [23].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although the optimal organic solvent concentration is less than typically used for CHO lysate precipitation [25, 26], this finding agrees with previous reports that 50% acetone is sufficient to precipitate most proteins greater than 20 kDa [21]. Conversely, Thongboonkerd et al have shown that a final organic solvent concentration of 90% was required to optimally precipitate urinary proteins [23].…”
Section: Discussionsupporting
confidence: 87%
“…Although research has previously demonstrated high recovery with less than 1 hr organic solvent incubation [21], incubation times for organic solvent precipitation typically range from several hours [25] to overnight [12, 24]. Decreasing precipitation incubation time can increase throughput without sacrificing protein recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Today's typical fed-batch bioprocess runs over 14 days, covering a variety of cellular states and environmental conditions, with obvious changes in growth rate, productivity, and, most importantly, product quality. The real power of -omics analysis is the ability to monitor these changes [78,79] and to generate an understanding of the needs of cells that enable them to generate high quality and value products [80].…”
Section: Transcriptomics Applicationsmentioning
confidence: 99%
“…Unfolded Protein Response (UPR) related genes such as X-box binding protein 1 (Xbp-1) (Cain et al, 2013), GADD34 and ATF4 have also been overexpressed and resulted increase in recombinant protein productivity. In order to reduce apoptosis, Bcl-XL, Mcl-1, MEM and Akt have all been overexpressed and improved culture longevity in various recombinant CHO cell lines (Arden et al, 2007;Carlage et al, 2012;Hwang and Lee, 2009;Majors et al, 2009). Additionally, some researchers successfully overexpressed genes that led to improved CHO cell growth or protein expression.…”
Section: Introductionmentioning
confidence: 98%